ANALISIS KUALITAS PELAYANAN KESEHATAN DI RSUD HARAPAN INSANI SENDAWAR KABUPATEN KUTAI BARAT : IMPLIKASINYA TERHADAP KEPUASAN PASIEN - Rusmini, Rusmini (PREDIKSI, 2016)
This study aims to determine the quality of health care and patient satisfaction in hospitals Harapan Insani West Kutai. Besides, this study also aims to determine the implications of the quality of health care to patient satisfaction in hospitals Harapan Insani West Kutai. The results showed that the prices Product Moment Correlation Coefficient (Pearson) of 0.592 at a significance level of 5%. These results were compared with the prices Critical contained in table r Product Moment Correlation (Pearson) at a significance level of 5% to N = 130 by .170, then the value is greater than the empirical r r theoretical value or 0.592> 0.170. Thus it can be concluded that there is a significant relationship of variable kuealitas service with variable patient. The results showed also that the t-test results is equal to 8.310 at a significance level of 5%. While t-theoretical value as shown in the table t-test contained in the annex to this paper shows the value of t for n - 2 (130-2 = 128) amounted to 1,979. Thus it can be said that t-empirical (8.310) is greater than the t-theoretical (1,979). Thus, there are significant and significant relationship between the variable quality of health services with variable patient satisfaction ..